Antimicrobial Properties and Mechanism of Action of Some Plant Extracts Against Food Pathogens and Spoilage Microorganisms - Gonelimali, Faraja D.; Lin, Jiheng; Miao, Wenhua; Xuan, Jinghu; Charles, Fedrick; Chen, Meiling; Hatab, Shaimaa R. (Frontiers in Microbiology, 2018)
This work aims to evaluate the antimicrobial potential of ethanolic and water extracts of roselle (Hibiscus sabdariffa), rosemary (Rosmarinus officin), clove (Syzygium aromaticum), and thyme (Thymus vulgaris) on some food pathogens and spoilage microorganisms. Agar well diffusion method has been used to determine the antimicrobial activities and Minimum Inhibitory Concentrations (MIC) of different plant extracts against Gram-positive bacteria (Bacillus cereus, Staphylococcus aureus), Gram-negative bacteria (Escherichia coli, Salmonella enteritidis, Vibrio parahaemolyticus, Pseudomonas aeruginosa), and one fungus (Candida albicans). The extracts exhibited both antibacterial and antifungal activities against tested microorganisms. Ethanolic roselle extract showed significant antibacterial activity (P<0.05) against all tested bacterial strains, while no inhibitory effect on Candida albicans (CA) was observed. Only the ethanolic extracts of clove and thyme showed antifungal effects against CA with inhibition zones ranging from 25.2±1.4 and 15.8±1.2 mm, respectively. Bacillus cereus (BC) appears to be the most sensitive strain to the aqueous extract of clove with a MIC of 0.315%. To enhance our understanding of antimicrobial activity mechanism of plant extracts, the changes in internal pH (pHin), and membrane potential were measured in Staphylococcus aureus (SA), and Escherichia coli (EC) cells after exposure to the plant extracts. The results indicated that the plant extracts significantly affected the cell membrane of Gram-positive and Gram-negative bacteria, as demonstrated by the decline in pHin as well as cell membrane hyperpolarization. In conclusion, plant extracts are of great value as natural antimicrobials and can use safely as food preservatives.